Oxalate determination in urine using an immobilized enzyme on Sorghum vulgare seeds in a flow injection conductimetric system - Oliveira Neto, Graciliano de; Tubino, Matthieu; Godinho, Oswaldo Espirito Santo; Kubota, Lauro Tatsuo; Fernandes, João Roberto [UNESP] (FapUNIFESP (SciELO), 1997)
A flow-injection (FI) method was developed for the determination of oxalate in urine. It was based on the use of oxalate oxidase (E.C. 1.2.3.4) immobilized on ground seeds of the BR-303 Sorghum vulgare variety. A reactor was filled with this activated material, and the samples (200 μL) containing oxalate were passed through it, carried by a deionized water flow. The carbon dioxide produced by the enzyme reaction permeated through a microporous PTFE membrane, and was received in a water acceptor stream, promoting conductivity changes proportional to the oxalate concentration in the sample. The results obtained showed a useful linear range from 0.05 to 0.50 mmol dm-3. The proposed method, when compared with the Sigma enzymatic procedure, showed good correlation (Y = 0.006(±0.016) + 0.98(±0.019)X; r = 0.9995, Y = conductivity in μS, and X = concentration in mmol dm-3), selectivity, and sensitivity. The new immobilization approach promotes greater stability, allowing oxalate determination for 6 months. About 13 determinations can be performed per hour. The precision of the proposed method is about ± 3.2 % (r.s.d).
Keywords: Conductimetry; Enzyme immobilization; Flow injection; Oxalate determination; Oxalate oxidase; Sorghum vulgare